Pembekalan Pengetahuan Soft Skill Siswa Dalam Mengelola Media Pembelajaran Di Mtsn Safinatussalamah Blang Panyang - Nuraini Fatmi fatmi; Iryana Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Soft skills in an effort to shape the character of students, the learning strategy that can be developed is to optimize the interaction between teachers and students, students and students, teachers and students and the environment as well as many-way interactions. This service aims to describe how to manage learning media through character-based learning. The implementation method is to use a field survey method by determining partner problems. The results and discussion of the soft skills development service activities for MTsN Safinatussalamah students are: that soft skills are skills that are not visible to the naked eye and basically soft skill attributes have been possessed by someone with different amounts and levels that can be improved and developed. This is strongly influenced by the habit of thinking, saying, acting and behaving, if the person concerned wants to change it by getting used to it. So that one day when it becomes a habit it will turn into the character of that person. So the main conclusion of this service is that through appropriate learning strategies, soft skills can be integrated into the learning process, so that students can develop soft skills in all aspects of learning at school.